“Influencia de las patalogías del cordón umbilical en el apgar del recién nacido en el hospital II – IPSS Tarapoto periodo 1995” - Fasanando Merino, Norma (1997)
This is a cohort study in the Hospital 11 IPSS Tarapoto during 1995 ring, where 958 births occurred, were studied 160 cases of changes of umbilical cord, with a 5.91 ·frecuencia... Found pathologies, were circular (95.6 /.) knots (1.3%), false knot (2.5 /.) · And sinuosity (0.6 /.); the demographic profile of the patient are, average age of 25,87 aAos, degree of instruction acceptable, State civil married, urban proced•ncia, occupation ~ ma House, gestational age at term. Factors associated with pathologies were: parity (P = 0, 0451), the R.N. male sex (P = 0, 0396), long umbilital cord (P = 0, 00000), visit to the sobaderas (P ~ 0.000). Met direct influence of alterations of the umbilical cord in the newborn State respectively. the (P = 0,0012 minute Apgar score and in the and P = 0, 0248) · The morbidity associated with greater frequency were neonatal infections, variance could not be found with the FrecueMcia Card...